Biocatalysts from alkaloid producing plants. (April 2016) - Kries, Hajo; O'Connor, Sarah E
Graphical abstract: Highlights: Secondary metabolism of plants serves as a rich source for bioactive molecules. Alkaloid biosynthetic pathways are revealing remarkable new enzymatic reactions. Enzymes in alkaloid biosynthesis allow access to a variety of applications in biocatalysis and bioengineering. Alkaloid pathways can be assembled in microorganisms that are tailored to the needs of medicinal chemistry. Abstract : Metabolic pathways leading to benzylisoquinoline and monoterpene indole alkaloids in plants are revealing remarkable new reactions. Understanding of the enzymes involved in alkaloid biosynthesis provides access to a variety of applications in biocatalysis and bioengineering. In chemo-enzymatic settings, plant biocatalysts can transform medically important scaffolds. Additionally, synthetic biologists are taking alkaloid pathways as templates to assemble pathways in microorganisms that are tailored to the needs of medicinal chemistry. In light of these many recent discoveries, it is expected that plants will continue to be a source of novel biocatalysts for the foreseeable future.